PENGARUH LINGKUNGAN MASYARAKAT TERHADAP PENGEMBANGAN KARAKTER ANAK USIA DINI - Nur Fitri, Kania Adinda (UNIVERSITAS SLAMET RIYADI, 2024)
Early childhood character, does not just happen. Early childhood character formation in influenced by environmental factors that shape children’s character, be it in the family environment, school, peers, and society. The community environment is an environment that is close to the child is part of the community where they live, so the character formation of the child will be adjusted to the norms, customs, and regulations in the community where the child lives. Therefore, it is important for adults around children to create a conductive and child-friendly community environment, so that children’s character formation will run well.